METHODOLOGY OF TEACHING LIGHT INDUSTRY SUBJECTS IN DISTANCE LEARNING ENVIRONMENT (World Bulletin of Education and Learning, 2025)
This article is devoted to the analysis of the process of teaching light industry subjects in a distance learning environment as a socio-pedagogical problem. The development of distance learning and its effective use are gaining urgent importance in the modern education system. The article studies the possibilities of the distance learning environment, technological approaches, issues of interaction between students and teachers, and factors affecting the quality of education.
Keywords: Distance learning environment, higher education, specialized disciplines, quality of education, technological approach, communication between students and teachers.